PROBLEMS OF TEACHING FOREIGN LANGUAGES - Inoyatova Dilnoza Ilhomovna (Лучшие интеллектуальные исследования, 2023)
Abstract. Under the motto "In a new Uzbekistan - a new worldview", new and innovative ideas are being promoted in a wide range of areas, and education policy is no exception. It is commendable that researches and consultations are being carried out in this field, but in order to develop, it is more important than ever to know and solve the problems of the system of foreign languages and their replacement.